Cancer incidence among employees in one mineral wool production plant in Denmark. - Olsen, Jørgen H.; Jensen, Ole M. (Scandinavian Journal of Work, Environment & Health, 1984)
The initiating hypothesis of the present study was that exposure to respirable fibers from mineral wool in concentrations seen at the place of production is carcinogenic to the respiratory system. In a test of this hypothesis 5,369 employees in the mineral wool production plant in question were followed from first employment at the plant until day of death or until the end of 1977. The factory started producing mineral wool in 1937 and the Danish Cancer Registry started working on a nationwide scale in 1943; therefore there was a maximum 40 years' duration of employment and 35 years' follow-up in the Cancer Registry. The observed numbers of cancer cases were compared with the expected numbers calculated on the basis of the age-, sex-, and time-specific incidence rates for cancer among the Danish population. Within the study period the Registry received notification of 136 cohort members with one cancer and 4 with two primary cancers, ie, a total of 144 cancer cases was observed against the 133.8 expected. Among workers with 20 or more years from first employment in the plant a significant excess of cancer of the lungs, bladder, and skin was found (observed versus expected cases: 9 vs 4.3, 4 vs 1.6 and 5 vs 2.4, respectively). This study thus supports the working hypothesis of an association between lung cancer and mineral wool production when the latency period for this type of cancer is taken into consideration.